Pengaruh Gaya Hidup Terhadap Perilaku Impulse Buying Dengan Literasi Maqashid Syariah Sebagai Variabel Moderating (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Islam UIN Sumatera Utara Medan) - Fajri, Muhammad Aulia; Arif Lubis, Fauzi; Ikhsan Harahap, Muhammad (Universitas Hamzanwadi, 2024)
The aim of this research is to examine the influence of lifestyle on impulse buying behavior with Maqashid Syariah literacy as a moderating variable. The study technique is descriptive quantitative, and 100 UIN North Sumatra Faculty of Economics and Islamic Business students who utilize E-commerce were surveyed. Online Google Forms questions generate data for regression path analysis. Research shows numerous important conclusions: 1. Lifestyle has a significant effect on impulse buying with a coefficient of 0.217 based on path analysis. 2. Lifestyle also has a significant effect on Maqashid Syariah literacy with a coefficient of 0.604. 3. Maqashid Syariah literacy has a significant influence on impulse buying of 0.539. 4. Simultaneously, Maqashid Syariah lifestyle and literacy influence impulse buying based on regression tests and path analysis